Pemasaran Jasa Pendidikan dan Implementasinya sebagai Strategi Pengembangan Pendidikan di SMP Muhammadiyah 1 Depok Sleman Yogyakarta - Muhammad Iqbal (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2019)
This research focused on the experience of Muhammadiyah Junior High School I (SMP 1) in Depok Sleman Yogyakarta in improving students trust and choice to study in the institution through an education marketing strategy. How the strategy of marketing is developed and work for educational services and its implementation is highlighted in this study. Using a qualitative research this paper utilizes the marketing strategy theory approach to educational services. The data were collected through: (1) observation, (2) documentation, and (3) in-depth interviews with school principals, public relations staff, student affairs, parents and students. It was validated by using source and technical triangulation technique in a qualitative research. The results of the study indicated that: First, the marketing strategy of educational services in improving the educational services in SMP 1 Muhammadiyah Depok, involves: (1) internal, (2) external, and (3) interactive marketing strategies. Second, the implementation of marketing strategies in improving education services in SMP 1 Muhammadiyah Depok covers: (1) implementing market selection strategies by segmenting the market, targeting and positioning. (2) establishing the marketing mix by applying quality products from this junior high school, highlighting its geographical location, applying competitive prices, and carrying out promotional steps. Third, the supporting and inhibiting factors of the marketing strategy in the school were summarized in the strengths, weaknesses, opportunities and threats (SWOT) analysis.